QUR'ANICVERSES TRANSLATION SEEN FROM PERSPECTIVE OF THEIR SENSITIVITY - Yuwono, Dolar (Universitas Sebelas Maret, 2013)
This paper discusses the translation quality of quranic verses from the pointÂ of view of their sensitivity. As containing many values and ways of life theÂ problem that the people are facing is how to understand the values that existÂ in, between and beyond the lines of the Quran verses. The question is whetherÂ translation and interpretation can answer it. As a matter of fact, Qurâ€™an versesÂ have sensitivity to be responded in the form of the translated texts. TheÂ translated texts of Qurâ€™an can be sensitive and controversial. SeveralÂ translation version of quranic verses were taken as data to see the level ofÂ their sensitivity which can be seen from some aspect: that it may be contraryÂ (1) to the state, (2) to religion (in a broad sense to the culture), (3) to decency,Â and (4) to private citizens. This category leads to a concomitant quartet ofÂ grounds for censorship: sedition, blasphemy, obscenity, and libel. The wordÂ â€œYaddullahâ€ in the section of â€œAl fath -verse-10â€, for example, from theÂ perspective of the contextual content of the text, would have becomeÂ dichotomical meaning or even multicotomical ones. The first one tends to useÂ the foriegnization, while the second tends to use domestication. Those whoÂ defend the word â€œYaddunâ€ as â€œthe handâ€ or â€œtanganâ€ as its word equivalenceÂ want to make their translation original not going out of the context of IslamicÂ teaching. They believe that those who have gone out of Islamic teachingÂ include unbelievers (that reject faith) and idolaters. The translation ofÂ â€œyadduâ€ into â€œhandâ€ or â€œtanganâ€ , according to some Muslims, contains theÂ implication that the translator has its implied lack of respect for the original text, and because of the defeatist view of the ability of the target audience which entails.On the other hand, those who have translated that word â€œyaddunâ€ into â€œpowerâ€ or â€œkekuasaanâ€ think that the translation into â€œhandâ€ or â€œtanganâ€ will disrupt and distort the image of God (Allah) existence. They are afraid that people think God is like human being having hands, head, legs and other part of the human body. Qurâ€™an as a Godâ€™s text which was revealed to the Prophet Muhammad via the archangel Gabriel, and intended for all times and all places needs to be perceived carefully because many of its verses are still stated in the forms of general statement. They need to be translated and interpreted in a way that makes people live peacefully, not on the other way around. The deference point of view in understanding Qurâ€™an verses must be supposed to be something that makes perspective of Muslims wide and tolerant.Â Â